Nedosiran safety and efficacy in PH1: interim analysis of PHYOX3 - Groothoff, Jaap; Sellier-Leclerc, Anne-Laure; Deesker, Lisa; Bacchetta, Justine; Schalk, Gesa; Tönshoff, Burkhard; Lipkin, Graham; Lemoine, Sandrine; Bowman, Thomas; Zhou, Jing; Hoppe, Bernd (Kidney international. Reports, 2024)
Introduction - Primary hyperoxaluria (PH) is a rare genetic disorder of hepatic glyoxylate metabolism. Nedosiran is an RNA interference (RNAi) therapeutic that the US Food and Drug Administration has approved for treatment of PH1. PHYOX3 is a trial evaluating monthly nedosiran in patients with PH. - Methods - In this PHYOX3 interim analysis, participants with PH1 who continued from a single-dose nedosiran trial (PHYOX1), with no previous kidney or liver transplantation, dialysis, or evidence of systemic oxalosis were eligible. The safety and efficacy of once-monthly nedosiran was assessed over 30 months. - Results - Thirteen participants completed PHYOX1 and continued into PHYOX3. At baseline, the mean (SD) and median (range) age was 24.2 (6.6) years and 23.0 (14-39) years, respectively; 53.8% were female and 61.5% were White. Mean estimated glomerular filtration rate (eGFR) remained stable (62-84.2 mL/min per 1.73 m2) to month 30. Mean 24-hour urinary oxalate (Uox) excretion showed a sustained reduction from baseline of ≥60% at every visit (months 2-30). From month 2, at least 10 of 13 (76.9%) participants achieved normal (<0.46 mmol/24h; upper limit of assay-normal [ULN]) or near-normal (≥0.46 to <0.60 mmol/24h; ≥ULN to <1.3 × ULN) 24-hour Uox excretion. All participants experienced ≥1 adverse event (AE), mostly mild or moderate in severity (primarily, injection site events). Three serious, not treatment-related AEs were reported; there were no deaths or study discontinuations due to AEs. - Conclusion - Nedosiran was well-tolerated in patients with PH1, and treatment resulted in a sustained, substantial reduction in Uox excretion for at least 30 months in this long-term study. No safety signals have been identified to date. The PHYOX3 study is ongoing.
Gesehen am 22.01.2025